Teaching Strategies for Students with Learning Disabilities (LD): Second and Fourth Grade at Thamer Mabrouk Primary School in M’sila-Algeria as a Case Study - bouakaz, amel (Journal of Social Sciences and Humanities, 2025)
The inclusion of students with special needs in mainstream education has been a significant focus, aiming to provide them full access to educational materials and social interactions. Despite the desire to include students with disabilities, teachers often lack the skills to address their needs effectively. This research aims to enhance educators' understanding of strategies for successful inclusive classrooms. It explores various teaching techniques to foster such environments. Consequently, the objective of this research is to explore various teaching techniques that educators can employ to foster a thriving inclusive classroom. This study aimed to answer the following research questions: What is a learning disability? What causes a learning disability? What are the characteristics of a student with a learning disability? And How can teachers ensure the successful integration of students with disabilities?. To gather data for this research, an analysis of academic literature and observations in two primary school classes was conducted. The study's findings highlighted that well-informed teachers utilize a range of teaching methods, including initial preparations and readiness. Similar to learning a new language, these strategies seamlessly integrate into contemporary discussions on effective teaching and learning. A specific set of guidelines, including working together with teaching assistants and other methods, can contribute to the academic achievement of children with special requirements.